2020
DOI: 10.3390/diagnostics10040189
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Platelet-Rich Plasma Injection in Rotator Cuff Tendinopathy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: To investigate the effectiveness of platelet-rich plasma (PRP) injection among patients with rotator cuff tendinopathy in comparison with sham injection, no injection, or physiotherapy alone. Methods: From the earliest records to November 1, 2018, all published or unpublished randomized controlled trial (RCTs) comparing PRP injection with a control group (sham injection, no injection, or physiotherapy alone) in patients with rotator cuff tendinopathy were included. Eligible trials were included fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
4
35
2
6
Order By: Relevance
“…Several studies have indicated little to no pain relief in patients treated for tendinosis pathologies or rotator cuff tears [ 143 , 144 ]. In contrast, several other studies indicated that PRP reduced or even eliminated pain in patients suffering from tendinosis, OA, plantar fasciitis, and other foot and ankle disorders [ 145 , 146 ]. The final platelet concentration and the biocellular composition have been identified as key PRP characteristics that contributed to the consistent analgesic effects observed after PRP applications.…”
Section: Prp Analgesic Effectsmentioning
confidence: 99%
“…Several studies have indicated little to no pain relief in patients treated for tendinosis pathologies or rotator cuff tears [ 143 , 144 ]. In contrast, several other studies indicated that PRP reduced or even eliminated pain in patients suffering from tendinosis, OA, plantar fasciitis, and other foot and ankle disorders [ 145 , 146 ]. The final platelet concentration and the biocellular composition have been identified as key PRP characteristics that contributed to the consistent analgesic effects observed after PRP applications.…”
Section: Prp Analgesic Effectsmentioning
confidence: 99%
“…В целом они демонстрируют значимое (в сравнении с использованием плацебо) уменьшение боли и улучшение функции после курсового применения ГлК и ОТП, особенно при длительном наблюдении (≥6 мес.) [14,15]. В то же время имеются лишь единичные работы, в которых сравнивался терапевтический потенциал этих препаратов при данной патологии [16].…”
Section: Comparison Of the Effectiveness Of Subacromial Administratiounclassified
“…Так, М. Lin и соавт. [14] провели метаанализ 5 РКИ (n=283), в которых лечебное действие ОТП сравнивалось с плацебо (локальное введение физиологического раствора (ФР)), отсутствием лечения и физиотерапией. В трех исследованиях анальгетическое действие активной терапии было более выраженным через 12 нед.…”
Section: терапияunclassified
See 1 more Smart Citation
“…Especially the numerous positive results from the conservative PRP treatment of joints, justify a continuous investigation of the PRP issue. The overwhelming amount of available data is retrospective; this, however, leads to some meta-analyses on this topic comparing PRP to corticosteroids for mostly orthopedic procedures [ 11 13 ], again showing some benefit. Currently, there is no other data, apart from our previous work, towards a PRP application in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%